Composite solidifying agent modified fly ash-gangue subgrade material and preparation method thereof

CN122878104APending Publication Date: 2026-10-09HUANENG LUOYUAN POWER GENERATION CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611045790.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]为了克服上述现有技术的缺点,本发明的目的在于提供一种复合固化剂改良粉煤灰-煤矸石路基料及其制备方法,以解决如何在极低固化剂掺量下,通过复合固化剂与粉煤灰-煤矸石混合料的协同反应,显著提高路基料的力学性能、抗变形能力和水稳定性,同时满足极重交通荷载要求并有效控制膨胀变形的技术问题

Benefits of technology

本发明公开的一种复合固化剂改良粉煤灰-煤矸石路基料的制备方法,通过两阶段加水闷料工艺,先加第一份水与煤矸石拌合闷料,使煤矸石预先充分吸水膨胀,再与粉煤灰、复合固化剂及第二份水混合搅拌,配合后续成型养护,实现了预膨胀抑制与化学固化双重协同作用。该方法中,复合固化剂(硅酸钠、氯化钙、氯化镁、聚丙烯酰胺和甲基纤维素)在0.3~0.6份极低掺量下即可与粉煤灰-煤矸石混合料反应生成钙矾石晶体和硅酸凝胶:钙矾石晶体填充混合料内部孔隙,使结构更加密实,同时抑制水分迁移,有效降低浸水膨胀率,实施例1仅为0.18%,远低于对比例1的0.54%;硅酸凝胶具有良好的胶结性能,将分散的颗粒牢固胶结为整体,显著提高结构强度。实施例1,两者协同增强,使7d抗压回弹模量高达132.7MPa,远高于JTG D50-2017规定的极重交通荷载路基回弹模量不小于70MPa的要求。同时,固化剂掺量仅为0.4份,相比对比例2固化剂用量10份,固化剂成本降低90%以上,且完全避免了水泥等高碳排材料的使用,工艺简单可控,适合大规模工业化生产和现场施工。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878104A_ABST
    Figure CN122878104A_ABST
Patent Text Reader

Abstract

The application discloses a composite solidifying agent improved fly ash-gangue roadbed material and a preparation method thereof, and belongs to the technical field of building materials, and is prepared from the following raw materials in parts by mass: 70-78 parts of gangue, 20-28 parts of fly ash, 0.3-0.6 parts of a composite solidifying agent, and the balance of water; the composite solidifying agent comprises sodium silicate, calcium chloride, magnesium chloride, polyacrylamide and methyl cellulose; the composite solidifying agent and the fly ash-gangue mixture react to generate ettringite crystals and silica acid gel. The composite solidifying agent has a very low dosage and a significant cost advantage, and the use of high-carbon-emission materials such as cement is avoided, and the low-carbon environmental protection advantage is prominent; the road performance is excellent, the extremely heavy traffic load requirement is met, the compression resilience modulus of 132.7 MPa can be reached after 7 days of maintenance, which is much higher than the requirement that the resilience modulus of the roadbed under the extremely heavy traffic load is not less than 70 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically relating to a composite curing agent-modified fly ash-coal gangue roadbed material and its preparation method. Background Technology

[0002] Coal gangue is the main solid waste generated during coal mining and sorting. The annual discharge of coal gangue is large, but the utilization rate is low. Large-scale accumulation causes serious environmental pollution. Using coal gangue for highway subgrade filling can not only dispose of solid waste, but also replace natural crushed stone resources, which has significant economic and environmental value. However, raw coal gangue has technical defects such as low fine particle content, poor gradation, difficulty in compaction, easy expansion when exposed to water, and insufficient strength, making it difficult to directly meet the subgrade performance requirements of high-grade roads, especially those with heavy traffic and extremely heavy traffic loads.

[0003] There are existing studies on using curing agents to improve coal gangue mixtures. For example, Chinese patent application CN114560669A discloses a curing agent-stabilized coal gangue mixture for road base courses and its preparation method. The curing agent is composed of multiple components such as cement, fly ash, slag powder, gypsum, steel slag, solid epoxy resin, regulator, and activator. The curing agent dosage is as high as 5-10 parts by weight (relative to 90-95 parts of coal gangue aggregate). The curing agent dosage is large and the composition is complex. Furthermore, it does not fully utilize the improvement effect of fly ash on the particle size distribution of coal gangue, nor does it reveal the microscopic reinforcement mechanism between the curing agent and the mixture. The curing efficiency needs to be improved. In addition, the technical problem of coal gangue swelling when exposed to water has not been solved, which has an adverse effect on the long-term stability of the roadbed. Chinese patent application CN119661163B discloses a method for preparing roadbed materials based on coal gangue, using 30-35 parts of silicate cement as a cementing material. This method involves a large amount of cement, resulting in high carbon emissions. Furthermore, the introduction of organic components such as sodium carboxymethyl cellulose increases costs and fails to address the core issues of efficient utilization of curing agents and low-carbon environmental protection.

[0004] In summary, existing roadbed materials have high curing agent or cement content, high cost, and large carbon emissions. They also fail to effectively solve the problems of coal gangue swelling when exposed to water and insufficient long-term water stability. There is an urgent need for a coal gangue roadbed material with extremely low curing agent content, significant cost advantage, excellent road performance, and effective control of expansion and deformation, as well as its preparation method. Summary of the Invention

[0005] In order to overcome the shortcomings of the prior art, the present invention aims to provide a composite curing agent-modified fly ash-coal gangue roadbed material and its preparation method, so as to solve the technical problem of how to significantly improve the mechanical properties, deformation resistance and water stability of the roadbed material through the synergistic reaction of the composite curing agent and the fly ash-coal gangue mixture at extremely low curing agent dosage, while meeting the requirements of extremely heavy traffic loads and effectively controlling expansion deformation.

[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing fly ash-coal gangue roadbed material modified by composite curing agent, comprising: crushing and screening coal gangue, adding a first portion of water and mixing evenly, allowing the material to sit, mixing it with fly ash, composite curing agent and a second portion of water, stirring evenly, molding it into a mold and then demolding it, and after curing, obtaining fly ash-coal gangue roadbed material modified by composite curing agent; The composite curing agent improves the fly ash-coal gangue roadbed material, which, by mass parts, includes: 70-78 parts of coal gangue, 20-28 parts of fly ash, 0.3-0.6 parts of composite curing agent, and the balance is water; the composite curing agent contains sodium silicate, calcium chloride, magnesium chloride, polyacrylamide and methylcellulose; the composite curing agent reacts with the fly ash and coal gangue mixture to generate ettringite crystals and silica gel.

[0007] Preferably, the amount of the first portion of water is 50% to 70% of the total water volume; the amount of the second portion of water is 30% to 50% of the total water volume.

[0008] Preferably, the curing time is 20 to 28 hours.

[0009] Preferably, the curing conditions include: a curing temperature of 20±1℃, a relative humidity of ≥95%, and a curing time of 7 to 28 days.

[0010] Preferably, the fly ash is Grade III fly ash with a density of 2.30–2.45 g / cm³. 3 The fineness is 30%–40%, and the average particle size is 40–50 μm.

[0011] Preferably, the coal gangue has a continuous particle size distribution of 1–20 mm, and the content of fine particles with a particle size less than 0.075 mm is ≤1.5%.

[0012] Preferably, in the composite curing agent, the mass ratio of sodium silicate, calcium chloride, magnesium chloride, polyacrylamide and methylcellulose is (30-50):(15-25):(10-20):(5-10):(5-10).

[0013] The present invention also discloses a composite curing agent modified fly ash-coal gangue roadbed material, which is prepared by the above-mentioned method for preparing the composite curing agent modified fly ash-coal gangue roadbed material.

[0014] The present invention also discloses the application of the above-mentioned composite curing agent-modified fly ash-coal gangue roadbed material in roadbed filling.

[0015] Preferably, the composite curing agent improves the 7-day compressive resilience modulus of fly ash-coal gangue roadbed material to ≥70MPa and the water immersion expansion rate to ≤0.3%.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing fly ash-coal gangue roadbed material modified with a composite curing agent. Through a two-stage water-addition and curing process, firstly, a first portion of water is added to the coal gangue and mixed to allow the gangue to fully absorb water and expand beforehand. Then, the gangue is mixed with fly ash, a composite curing agent, and a second portion of water. Combined with subsequent molding and curing, this achieves a synergistic effect of pre-expansion inhibition and chemical curing. In this method, the composite curing agent (sodium silicate, calcium chloride, magnesium chloride, polyacrylamide, and methylcellulose) reacts with the fly ash-coal gangue mixture at an extremely low dosage of 0.3–0.6 parts to generate ettringite crystals and silica gel. The ettringite crystals fill the internal pores of the mixture, making the structure denser, while simultaneously inhibiting moisture migration and effectively reducing the immersion expansion rate (only 0.18% in Example 1, far lower than 0.54% in Comparative Example 1). The silica gel has excellent bonding properties, firmly binding the dispersed particles into a whole, significantly improving structural strength. Example 1 demonstrates how the two materials synergistically enhance the 7-day compressive resilient modulus to a high level of 132.7 MPa, far exceeding the requirement of at least 70 MPa for roadbeds under extremely heavy traffic loads as specified in JTG D50-2017. Simultaneously, the curing agent dosage is only 0.4 parts, compared to 10 parts in Comparative Example 2, resulting in a curing agent cost reduction of over 90%. Furthermore, the use of high-carbon-emission materials such as cement is completely avoided. The process is simple and controllable, suitable for large-scale industrial production and on-site construction.

[0017] This invention discloses a composite curing agent to improve fly ash-coal gangue roadbed material. Using coal gangue and fly ash, two industrial solid wastes, as the main raw materials, it achieves a high total utilization rate of solid waste, significantly reducing raw material costs and solving the land occupation and environmental pollution problems caused by coal gangue accumulation. By optimizing the particle size distribution of coal gangue through fly ash admixture, the density and workability of the mixture are improved. Combined with a composite curing agent containing sodium silicate, calcium chloride, magnesium chloride, polyacrylamide, and methylcellulose, the dosage is only 0.3–0.6 parts. Under normal temperature conditions, it reacts with the mixture to generate ettringite crystals and silica gel, achieving efficient chemical curing. The curing agent dosage is extremely low, resulting in significant cost advantages; it completely eliminates the use of cement, making it low-carbon and environmentally friendly; and it exhibits excellent mechanical properties, with a 7-day compressive resilience modulus ≥70MPa and a water immersion expansion rate ≤0.3%, meeting the requirements for extremely heavy traffic load levels. It is a new type of roadbed material that combines economy, environmental friendliness, and high performance.

[0018] This invention discloses the application of a composite curing agent-modified fly ash-coal gangue subgrade material in roadbed filling. In Example 1, the 7-day unconfined compressive strength of the fly ash-coal gangue subgrade material modified by the composite curing agent of this invention reaches 1.12 MPa, and the bearing capacity ratio is as high as 142.8%, which is comparable to the bearing capacity ratio of 145.2% in Comparative Example 2, but the amount of curing agent used is only 1 / 25 of that in Comparative Example 2. The water immersion swelling rate is only 0.18%, which is far better than 0.54% in Comparative Example 1 and 0.32% in Comparative Example 2, effectively solving the technical problem of subgrade deformation caused by the swelling of coal gangue when exposed to water, and ensuring the stability and durability of the subgrade in long-term service. At the same time, the 7-day compressive resilient modulus of 132.7 MPa is far higher than the 70 MPa requirement specified in JTG D50-2017, which means that the subgrade material can reach or even exceed the design strength in a short period of time, significantly shortening the construction period. Attached Figure Description

[0019] Figure 1 This is a schematic diagram of the preparation method of the improved fly ash-coal gangue roadbed material by the composite curing agent of the present invention. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.

[0022] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.

[0023] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.

[0024] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.

[0025] In this invention, unless otherwise specified, the numerical range "a~b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply an abbreviation for these numerical combinations.

[0026] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.

[0027] The term “and / or” as used in this invention refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.

[0028] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.

[0029] This invention provides a fly ash-coal gangue roadbed mixture modified by a composite curing agent. This mixture achieves efficient curing by optimizing the coal gangue gradation through the critical fly ash dosage and using an extremely low composite curing agent dosage. Combined with the synergistic enhancement mechanism of ettringite crystals and silica gel and a two-stage water-addition curing process, it significantly improves the mechanical properties, deformation resistance, and water stability of the roadbed mixture, meeting the requirements of extremely heavy traffic load levels, while greatly reducing the amount of curing agent used and the cost.

[0030] The coal gangue used in this invention is a solid waste generated during coal mining and sorting. Its chemical composition is mainly SiO2 and Al2O3, with SiO2 content of 50% to 65% and Al2O3 content of 20% to 40%, and loss on ignition of no more than 15%. The total mass of SiO2 and Al2O3 in the coal gangue is not less than 70%.

[0031] The fly ash used in this embodiment is dry or wet fly ash from a coal-fired power plant, and the total mass of SiO2, Al2O3 and Fe2O3 in its chemical composition is not less than 70%, and the loss on ignition is not greater than 15%.

[0032] This invention provides a composite curing agent to improve fly ash-coal gangue roadbed material, which is composed of the following raw materials in parts by weight: 70-78 parts of coal gangue, 20-28 parts of fly ash, 0.3-0.6 parts of composite curing agent, and the balance being water; the composite curing agent contains sodium silicate, calcium chloride, magnesium chloride, polyacrylamide, and methylcellulose; the composite curing agent reacts with the fly ash-coal gangue mixture to generate ettringite crystals and silica gel.

[0033] In this invention, a composite curing agent reacts with a fly ash-coal gangue mixture to generate ettringite crystals and silica gel. The reaction mechanism is as follows: Sodium silicate in the composite curing agent interacts with calcium chloride in water to generate a large amount of silica gel and hydrated calcium silicate gel. This gel material encapsulates and binds the fly ash and coal gangue particles, filling the pores between particles and making the mixture structure more compact. Calcium chloride and magnesium chloride in the composite curing agent, after dissolving in water, provide Ca... 2+ and Mg 2+ In fly ash, active Al₂O₃ dissolves aluminate ions in an alkaline environment, which then react with SO₄²⁻ in the system. 2- (Sulfates from coal gangue or fly ash) and Ca 2+ The reaction produces ettringite (AFt) crystals. These crystals grow within the pores of the mixture, filling them and inhibiting moisture migration. The silica gel acts as a binder, binding the dispersed particles together, while the ettringite crystals fill and compensate for expansion, creating a dense structure. The synergistic effect of both significantly improves the mechanical strength and water stability of the roadbed material.

[0034] The fly ash is classified as Grade III fly ash, with a density of 2.30–2.45 g / cm³. 3 The fineness is 30%–40%, and the average particle size is 40–50 μm; the particle size distribution of coal gangue is a continuous gradation of 1–20 mm, and the content of fine particles with a particle size less than 0.075 mm is ≤1.5%.

[0035] The mass ratio of each component in the composite curing agent is: 30-50 (sodium silicate): 15-25 (calcium chloride): 10-20 (magnesium chloride): 5-10 (polyacrylamide): 5-10 (methylcellulose).

[0036] The fly ash content is 25% by mass, and the composite curing agent content is 0.4 parts by mass.

[0037] This invention discloses a method for preparing a composite curing agent-modified fly ash-coal gangue roadbed material, comprising the following steps: 1) Crush and screen the coal gangue to a continuous gradation of 1-20mm; 2) Take all the coal gangue, add 50% to 70% of the total water, mix evenly, and let it sit for 20 to 28 hours; preferably, the sitting time is 24 hours, and the amount of water added is 60% of the total water. 3) Mix the coal gangue after curing with all the fly ash, all the composite curing agent, and the remaining 30% to 50% of water, and stir evenly for 3 to 5 minutes; 4) The mixture is molded to a compaction degree of 96%. After molding for 2 hours, the specimens are demolded and then placed in a standard curing chamber for curing. The curing temperature is 20±1℃, the relative humidity is ≥95%, and the curing time is 7 to 28 days.

[0038] The 7-day compressive resilient modulus of the mixture is ≥70MPa, and the water immersion expansion rate is ≤0.3%, which meets the performance requirements of subgrade for extremely heavy traffic loads.

[0039] This invention uses an extremely low amount of curing agent, resulting in a significant cost advantage. The composite curing agent dosage is only 0.4 parts, reducing the curing agent cost by more than 90%. Simultaneously, it avoids the use of high-carbon-emission materials such as cement, highlighting its low-carbon and environmentally friendly advantages. It exhibits excellent road performance, meeting the requirements of extremely heavy traffic loads. After 7 days of curing, it achieves a compressive resilience modulus of 132.7 MPa, far exceeding that of JTG. The D50-2017 standard requires a resilient modulus of not less than 70 MPa for subgrades subjected to extremely heavy traffic loads. Unconfined compressive strength, cohesion, internal friction angle, and bearing capacity ratio all show significant improvements with increasing curing agent dosage and curing time, resulting in overall road performance significantly superior to unmodified coal gangue. Expansion deformation is effectively controlled, and water stability is good. A two-stage water-addition and curing process pre-expands the coal gangue, allowing the ettringite crystals generated by the curing agent to fill pores and inhibit moisture migration, significantly reducing the water-immersion expansion rate. Drying shrinkage strain decreases significantly with increasing curing agent dosage, ensuring long-term subgrade stability. The mechanism is clear, and the process is controllable, revealing the technical chain from gradation improvement and ettringite / silica gel synergistic reinforcement to two-stage curing and swelling suppression. The performance of the mixture can be precisely controlled by adjusting the fly ash dosage, curing agent dosage, curing time, and curing regime, making it suitable for different grades of road engineering. Solid waste resource utilization is high, with the main raw materials, coal gangue and fly ash, being industrial solid waste, achieving a total utilization rate of over 95%.

[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0041] Example 1 This embodiment provides a fly ash-coal gangue roadbed mixture modified with a composite curing agent: Raw material ratio: coal gangue: 75 parts, fly ash: 25 parts, composite curing agent: 0.4 parts.

[0042] Total water consumption: 15.2% of the dry weight of the mixture.

[0043] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 60% of the total water (i.e., 9.12% of the dry weight of the mixture), mix well, and let it sit for 24 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 40% water (i.e., 6.08% water by dry weight of the mixture) to a forced mixer and mix for 4 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 7 days.

[0044] Example 2 Raw material ratio: coal gangue: 75 parts, fly ash: 25 parts, composite curing agent: 0.3 parts.

[0045] Total water consumption: 15.2% of the dry weight of the mixture.

[0046] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 60% of the total water (i.e., 9.12% of the dry weight of the mixture), mix well, and let it sit for 24 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 40% water (i.e., 6.08% water by dry weight of the mixture) to a forced mixer and mix for 4 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 28 days.

[0047] Example 3 Raw material ratio: coal gangue: 75 parts, fly ash: 25 parts, composite curing agent: 0.6 parts.

[0048] Total water consumption: 15.2% of the dry weight of the mixture.

[0049] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 60% of the total water (i.e., 9.12% of the dry weight of the mixture), mix well, and let it sit for 24 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 40% water (i.e., 6.08% water by dry weight of the mixture) to a forced mixer and mix for 4 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 7 days.

[0050] Example 4 Raw material ratio: coal gangue: 72 parts, fly ash: 28 parts, composite curing agent: 0.4 parts.

[0051] Total water consumption: 15.2% of the dry weight of the mixture.

[0052] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 60% of the total water (i.e., 9.12% of the dry weight of the mixture), mix well, and let it sit for 24 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 40% water (i.e., 6.08% water by dry weight of the mixture) to a forced mixer and mix for 4 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 28 days.

[0053] Example 5 This embodiment provides a fly ash-coal gangue roadbed mixture modified with a composite curing agent: Raw material ratio: coal gangue: 70 parts, fly ash: 20 parts, composite curing agent: 0.5 parts.

[0054] Total water consumption: 15.2% of the dry weight of the mixture.

[0055] The mass ratio of each component in the composite curing agent is: sodium silicate: calcium chloride: magnesium chloride: polyacrylamide: methylcellulose = 30:15:10:5:5.

[0056] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 50% of the total water (i.e., 7.6% of the dry weight of the mixture), mix well, and let it sit for 20 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 50% water (i.e., 7.6% water by dry weight of the mixture) to a forced mixer and mix for 3 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 7 days.

[0057] Example 6 This embodiment provides a fly ash-coal gangue roadbed mixture modified with a composite curing agent: Raw material ratio: coal gangue: 78 parts, fly ash: 24 parts, composite curing agent: 0.5 parts.

[0058] Total water consumption: 15.2% of the dry weight of the mixture.

[0059] The mass ratio of each component in the composite curing agent is: sodium silicate: calcium chloride: magnesium chloride: polyacrylamide: methylcellulose = 50:25:20:10:10.

[0060] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 70% of the total water (i.e., 10.64% of the dry weight of the mixture), mix well, and let it sit for 28 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 30% water (i.e., 4.56% water by dry weight of the mixture) to a forced mixer and mix for 5 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 14 days.

[0061] Example 7 This embodiment provides a fly ash-coal gangue roadbed mixture modified with a composite curing agent: Raw material ratio: coal gangue: 74 parts, fly ash: 26 parts, composite curing agent: 0.5 parts.

[0062] Total water consumption: 15.2% of the dry weight of the mixture.

[0063] The mass ratio of each component in the composite curing agent is: sodium silicate: calcium chloride: magnesium chloride: polyacrylamide: methylcellulose = 35:18:12:6:6.

[0064] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 55% of the total water (i.e., 8.36% of the dry weight of the mixture), mix well, and let it sit for 22 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 45% water (i.e., 6.84% water by dry weight of the mixture) to a forced mixer and mix for 3.5 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 21 days.

[0065] Example 8 This embodiment provides a fly ash-coal gangue roadbed mixture modified with a composite curing agent: Raw material ratio: coal gangue: 72 parts, fly ash: 22 parts, composite curing agent: 0.5 parts.

[0066] Total water consumption: 15.2% of the dry weight of the mixture.

[0067] The mass ratio of each component in the composite curing agent is: sodium silicate: calcium chloride: magnesium chloride: polyacrylamide: methylcellulose = 45:22:18:8:8.

[0068] The preparation method of the fly ash-coal gangue roadbed mixture modified by the composite curing agent includes the following steps: 1) The coal gangue is crushed and screened to obtain aggregates with a continuous gradation of 1-20 mm particle size; 2) Take all the coal gangue, add 65% of the total water (i.e., 9.88% of the dry weight of the mixture), mix evenly, and let it sit for 26 hours; 3) Add the cured coal gangue, all fly ash, all composite curing agent, and the remaining 35% water (i.e., 5.32% water by dry weight of the mixture) to a forced mixer and mix for 4.5 minutes until uniform. 4) Compact the mixture to 96% to form cylindrical specimens with a diameter of 150 mm and a height of 150 mm, and demold after 2 hours; 5) Place the specimens in a standard curing chamber at a temperature of 20±1℃ and a relative humidity of ≥95% for 28 days.

[0069] Comparative Example 1 Raw material ratio: coal gangue: 75 parts, fly ash: 25 parts.

[0070] Total water consumption: 15.2% of the dry weight of the mixture.

[0071] The method for preparing this roadbed mixture includes the following steps: No curing agent is added; water is added and mixed in one go; a two-stage curing process is not used; other molding and curing conditions are the same.

[0072] Comparative Example 2 Raw material ratio: Coal gangue: 90 parts, curing agent: 10 parts.

[0073] The method for preparing this roadbed mixture includes the following steps: Add water and mix at once; curing and shaping conditions are the same as above.

[0074] Performance testing According to JTG 3441—2024 "Test Procedures for Inorganic Binder Stabilized Materials in Highway Engineering" and JTG 3430—2020 "Test Procedures for Highway Geotechnical Engineering", the 7-day and 28-day unconfined compressive strength, 7-day compressive resilient modulus, water swelling rate (immersion for 4 days), and bearing capacity ratio (CBR) of each embodiment and comparative example were tested. The results are shown in Table 1.

[0075] Table 1. Performance Comparison of Examples and Comparative Examples

[0076] As shown in Table 1, in Example 1, the curing agent dosage was only 0.4 parts, and the 7-day compressive resilient modulus was 132.7 MPa, significantly higher than the requirement for extremely heavy traffic loads (≥70 MPa). Furthermore, the water immersion swelling rate was only 0.18%, far lower than Comparative Example 1 (0.54%) and Comparative Example 2 (0.32%), indicating that the two-stage water-addition and curing process effectively suppressed expansion. Although the 7-day unconfined compressive strength of Example 1 (1.12 MPa) was slightly lower than that of Comparative Example 2 (1.25 MPa), the curing agent dosage was only 1 / 25 of that of Comparative Example 2, demonstrating a clear cost-effectiveness advantage. Moreover, the 28-day strength increased to 1.38 MPa, approaching the 1.48 MPa of Comparative Example 2. Comparative Example 1, without the addition of curing agent and without the curing process, exhibited poor performance in all aspects and did not meet the requirements for the roadbed. Example 1 has a load-bearing ratio (142.8%) comparable to Comparative Example 2 (145.2%), but a lower immersion swelling rate, indicating that the present invention has a unique advantage in swelling control.

[0077] In summary, this invention discloses a composite curing agent-modified fly ash-coal gangue roadbed and its preparation method, comprising the following raw materials in parts by weight: 70-78 parts coal gangue, 20-28 parts fly ash, 0.3-0.6 parts composite curing agent, and the balance being water; the composite curing agent contains sodium silicate, calcium chloride, magnesium chloride, polyacrylamide, and methylcellulose; the composite curing agent reacts with the fly ash-coal gangue mixture to generate ettringite crystals and silica gel. This invention uses an extremely low amount of curing agent, resulting in significant cost advantages. The composite curing agent dosage is only 0.4 parts, reducing the curing agent cost by more than 90%, while avoiding the use of high-carbon emission materials such as cement, demonstrating outstanding low-carbon and environmentally friendly advantages; it exhibits excellent road performance, meeting the requirements of extremely heavy traffic loads, and achieving a compressive resilient modulus of 132.7 MPa after 7 days of curing, far exceeding the requirement of not less than 70 MPa for roadbeds under extremely heavy traffic loads as specified in JTG D50-2017.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a composite curing agent-modified fly ash-coal gangue roadbed, characterized in that, include: After crushing and screening the coal gangue, add the first portion of water and mix evenly. After curing, mix with fly ash, composite curing agent and the second portion of water, stir evenly, put into mold and demold. After curing, the composite curing agent improved fly ash-coal gangue roadbed material is obtained. The composite curing agent used to improve fly ash-coal gangue roadbed material comprises, by mass parts: 70-78 parts coal gangue, 20-28 parts fly ash, 0.3-0.6 parts composite curing agent, with the balance being water; the composite curing agent contains sodium silicate, calcium chloride, magnesium chloride, polyacrylamide, and methylcellulose; the composite curing agent reacts with the fly ash and coal gangue mixture to generate ettringite crystals and silica gel.

2. The preparation method of the composite curing agent-modified fly ash-coal gangue roadbed material according to claim 1, characterized in that, The first portion of water is used in quantities of 50% to 70% of the total water volume; the second portion of water is used in quantities of 30% to 50% of the total water volume.

3. The preparation method of the composite curing agent-modified fly ash-coal gangue roadbed material according to claim 1, characterized in that, The curing time is 20 to 28 hours.

4. The preparation method of the composite curing agent-modified fly ash-coal gangue roadbed material according to claim 1, characterized in that, The conditions for maintenance include: a maintenance temperature of 20±1℃, a relative humidity of ≥95%, and a maintenance time of 7 to 28 days.

5. The preparation method of the composite curing agent-modified fly ash-coal gangue roadbed material according to claim 1, characterized in that, The fly ash is Class III fly ash with a density of 2.30–2.45 g / cm³. 3 The fineness is 30%–40%, and the average particle size is 40–50 μm.

6. The preparation method of the composite curing agent-modified fly ash-coal gangue roadbed material according to claim 1, characterized in that, The coal gangue has a particle size distribution of 1-20 mm in a continuous gradation, and the content of fine particles with a particle size less than 0.075 mm is ≤1.5%.

7. The preparation method of the composite curing agent-modified fly ash-coal gangue roadbed material according to claim 1, characterized in that, In the composite curing agent, the mass ratio of sodium silicate, calcium chloride, magnesium chloride, polyacrylamide and methylcellulose is (30-50):(15-25):(10-20):(5-10):(5-10).

8. A composite curing agent for improving fly ash-coal gangue roadbed material, characterized in that, The material was prepared using the method described in any one of claims 1-7 for improving fly ash-coal gangue roadbed material with composite curing agent.

9. The application of the composite curing agent modified fly ash-coal gangue subgrade material as described in claim 8 in road subgrade filling engineering.

10. The application of the composite curing agent-modified fly ash-coal gangue subgrade material according to claim 9 in road subgrade filling, characterized in that, The composite curing agent improves the 7-day compressive resilience modulus of fly ash-coal gangue roadbed material to ≥70MPa and the water immersion expansion rate to ≤0.3%.

Citation Information

Patent Citations

  • Curing agent stabilized coal gangue mixture for road base and preparation method of curing agent stabilized coal gangue mixture

    CN114560669A

  • A roadbed material and method for preparing roadbed material based on coal gangue material

    CN119661163B